ISOLATION OPTIMIZATION OF 1?-ACETOXYCHAVICOL ACETATE FROM GALANGAL RHIZOME (ALPINIA GALANGA (L.) WILLD) USING VACUUM LIQUID CHROMATOGRAPHY METHOD - Adelia Monesi, Leony
Alpinia galanga (L.) Willd, or commonly called the 'Galangal' plant, is a spice type plant that widespread in the tropical regions of Southeast Asia, including Indonesia. This plant has various health benefits for human body. Phytochemically, galangal produces secondary metabolites of phenolic derivatives, the phenylpropanoid group. Previous studies reported that 1?-acetoxychavicol acetate (ACA) is a major component of this plant, and has been shown to have anticancer properties. In this research, optimization of ACA isolation from galangal rhizome has been conducted using liquid vacuum chromatography method with the research stages included extraction of rhizomes by maceration technique in acetone solvent, isolation and determination of the structure of ACA, and optimization of isolation of 1?-acetoxychavicol acetate (ACA) compound by fractionation using the KVC technique (liquid vacuum chromatography) using n-hexane:EtOAc 9:1 to EtOAc:Methanol 19:1 eluent, guided by TLC analysis (thin layer chromatography). The ACA molecular structure is determined based on UV and NMR spectra. Isolation optimization was done by varying the ratio of the mass of the sample to the mass of the adsorbent KVC (silica gel), which is 1:10 (KVC 1), 1,3:10 (KVC 2), and 1,8:10 (KVC 3). The optimization results showed the pure fraction mass from the ratio of 1:10; 1,3:10; 1,8:10 were 338,3 g (33,83%), 583,2 g (23,33%) and 510,5 g (10.21%), respectively. Percentage of total mass extracted from the ratio of 1:10; 1,3:10; 1,8:10 are 83,38%, 65,01% and 40,36%, respectively. Based on these results it can be concluded that the fractionation of the mass ratio of the sample to silica gel 1,3:10 produces the largest mass fraction that contains ACA. However, when based on the mass percentage of the eluted extract, the ratio of the mass of the sample to silica gel 1:10 has the highest ACA mass percent value.